OR Booking Policy: Development and Implementation - Kontak-Forsyth, Margot; Grant, Anne (Operating Room Nurses Association of Canada Journal, 1995)
Surgical bookings are integral to the optimal functioning of any operating room facility (OR).' Ideally, the goals and strategic planning of the organization should be reﬂected in surgical block scheduling. For example if an institution has identified that it intends to increase outpatient procedures or day surgery, it only follows that an appropriate amount of elective surgical time be allocated to any service or physicians who perform such procedures. Unfortunately this is not always recognized and often the process of booking OR 1ists is designated as merely a clerical function. In actual fact, bookings are the force that drives the OR. The authors will examine development and maintenance of a policy for this important area, and outline criteria which should be included in an optimal OR booking policy.